Stakeholder workshop on advancing veterinary medicines governance in Kenya - Moodley, Arshnee; Muloi, Dishon M. (International Livestock Research Institute, 2025)
This stakeholder workshop convened in June 2025 brought together regulators, academia, veterinary associations, producer groups, and livestock farmers. Participants discussed key challenges and opportunities in strengthening veterinary medicines governance and antimicrobial stewardship in Kenya. The dialogue focused on four interlinked themes: (i) policy harmonization and governance, (ii) regulation of the poultry value chain, (iii) feed quality and safety, and (iv) pharmaceutical industry practices and stewardship. Across sessions, participants emphasized that fragmented policy implementation, weak institutional coordination, and limited awareness among farmers and agrovets continue to hinder prudent antimicrobial use. Recommendations included harmonizing regulatory mandates, enhancing joint inspections, strengthening surveillance of feed and day-old chick supply chains, and ensuring consistent farmer engagement. The workshop concluded with a collective call to action: to embed antimicrobial stewardship within Kenya’s veterinary governance systems through coordinated national-county collaboration, private-sector accountability, and evidence-based policy reform.